VOCABULARY OF INTERNET COMMUNICATION (ON THE EXAMPLE OF ENGLISH AND UBEK LANGUAGES) - Ismoilova Kamola Rafikovna (Galaxy International Interdisciplinary Research Journal, 2023)
To identify the peculiarities of the vocabulary of Internet communication in English languages is the aim of this article. The characteristics of the materials found on the Internet sites are presented. The types of preferred Internet communication vocabulary are determined. They include abbreviations, erratives, and neologisms. It can be concluded that the vocabulary of Internet communication is constantly changing due to the emergence of new words and expressions.